2020
DOI: 10.48550/arxiv.2008.08725
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unraveling the role of V-V dimer on the vibrational properties of VO$_2$ by first-principles simulations and Raman spectroscopic analysis

Wasim Raja Mondal,
Egor Evlyukhin,
Sebastian A. Howard
et al.

Abstract: We investigate the vibrational properties of VO2, particularly the low temperature M1 phase by first-principles calculations using the density functional theory as well as Raman spectroscopy. We perform the structural optimization using SCAN meta-GGA functional and obtain the optimized crystal structures for metallic rutile and insulating M1 phases satisfying all expected features of the experimentally derived structures. Based on the harmonic approximation around the optimized structures at zero temperature, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
0
3
1
Order By: Relevance
“…[62] That the SCAN functional (without U) is incapable to open a bandgap for VO 2 (M1) strongly contradicts the experiment. [36] It also contradicts with our finding above, as well as what others [75] have observed with the same functional (Table 2). While the discrepancy between these results obtained from two different simulation codes requires further investigation, the results of our calculation suggest that meta-GGA SCAN functional coded in VASP has some ability to polarize the Fermi level.…”
Section: Bandgap Band Structure and Density Of Statescontrasting
confidence: 99%
“…[62] That the SCAN functional (without U) is incapable to open a bandgap for VO 2 (M1) strongly contradicts the experiment. [36] It also contradicts with our finding above, as well as what others [75] have observed with the same functional (Table 2). While the discrepancy between these results obtained from two different simulation codes requires further investigation, the results of our calculation suggest that meta-GGA SCAN functional coded in VASP has some ability to polarize the Fermi level.…”
Section: Bandgap Band Structure and Density Of Statescontrasting
confidence: 99%
“…For VO 2 , there have been previous studies of the energetics and electronic structures using the SCAN [30][31][32][33][34]. Notably, Mondal et al reported vibrational properties of VO 2 with SCAN functional [34].…”
Section: Introductionmentioning
confidence: 99%
“…For VO 2 , there have been previous studies of the energetics and electronic structures using the SCAN [30][31][32][33][34]. Notably, Mondal et al reported vibrational properties of VO 2 with SCAN functional [34]. Their phonon band of R-VO 2 with the SCAN is almost same as using GGA functional and does not exhibit an evidence for the Peierls-like structural distortion [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation